Strange folk eaudiobook A novel. - Dyer, Alli (Simon & Schuster Audio, 2024)
A woman returns to her estranged, magical family in Appalachia, where a conjuring meant to protect the community may have summoned something sinister in this lush and "bewitching debut" (Andrea Bartz, New York Times bestselling author) that is perfect for fans of Alice Hoffman, Deborah Harkness, and Sarah Addison Allen. Lee left Craw Valley at eighteen without a backward glance. She wanted no part of the generations of her family who tapped into the power of the land to heal and help their community. But when she abandons her life in California and has nowhere else to go, Lee returns to Craw Valley with her children in tow to live with her grandmother, Belva. Lee vows to stay far away from Belva's world of magic, but when the target of one of her grandmother's spells is discovered dead, Lee fears that Belva's magic may have conjured something far more sinister. As she searches for answers to protect her family, Lee travels down a rabbit hole of strange phenomena and family secrets that force her to reckon with herself and rediscover her power.